A estética do marketing: a propaganda como condutor na estratégia de diferenciação no varejo de eletrodomésticos brasileiro - Euler Alves Brandao (2011)
The retail of electronic goods in the Brazil is seen as one of the main economic sectors, if the investments in advertising are taken into account. This is a very concentrated and competitive sector and its members use advertising as a communication strategy and sales promotion. In this scenario Ricardo Eletro, a company from Minas Gerais state, shows a very significant growth, leaping from the 14th position to the 2nd in the sales ranking of this industry in five years. This survey checked the competitive strategies adopted by the company both on the entrepreneurial and functional level considering the vision of its principal strategist, aiming at identifying the elements that could explain such performance. A very special attention was given to its communication strategy, which is supposedly the singularity driver of the company in question due to the importance of advertising in its value chain and in its distinctive performance. Using quantitative and qualitative techniques, divided into two phases the first one, exploratory and the second, descriptive it was concluded that advertising, particularly the ads on TV, really influence the purchase and the image of the retail chains under survey. To reach this conclusion, a scale was devised in order to measure the construct image and the model ARM was used as a base to evaluate the effectiveness (persuasion), which allowed a comparison among the advertising campaigns of the main retail chains of this industry. This model predicts that the efficacy of advertising happens through the central and peripheral route of cognition. This fact confirmed the relevance of execution elements in advertising specially the aesthetic ones as promoters of persuasion, justifying the consideration of advertising as an aesthetic object, as well as the use of the term aesthetic marketing. As a result, it is observed that among the TV commercials researched, Ricardo Eletro was shown as the one with a very distinctive advertisement. Such conclusion indicates the significance of the survey when it proposes advertising as the element which makes all the difference in a competitive strategy, especially in the market analyzed, characterized by shopping goods.